Effects of exercise on circadian rhythms and mobility in aging Drosophila melanogaster - Rakshit, Kuntol (2013)
Daily life functions such as sleep and feeding oscillate with circa 24 h period due to endogenous circadian rhythms generated by circadian clocks. Genetic or environmental disruption of circadian rhythms is associated with various aging-related phenotypes. Circadian rhythms decay during normal aging, and there is a need to explore strategies that could avert age-related changes in the circadian system. Exercise was reported to delay aging in mammals. Here, we investigated whether daily exercise via stimulation of upward climbing movement could improve circadian rest/activity rhythms in aging Drosophila melanogaster. We found that repeated exercise regimen did not strengthen circadian locomotor activity rhythms in aging flies and had no effect on their lifespan. We also tested the effects of exercise on mobility and determined that regular exercise lowered age-specific climbing ability in both wild type and clock mutant flies. Interestingly, the climbing ability was most significantly reduced in flies carrying a null mutation in the core clock gene period, while rescue of this gene significantly improved climbing to wild type levels. Our work highlights the importance of period in sustaining endurance in aging flies exposed to physical challenge.